Death in custody : inquests, family participation and state accountability - Easton, Jo (Bingley, U.K. : Emerald Publishing Limited, 2020)
Death in Custody considers the participation of bereaved families in an inquest following a death in custody. It looks at the legal frameworks governing participation, as well as relevant theories of justice, participation, procedural fairness and grief theory. Interviews were carried out with people with personal experience of complex inquests, including bereaved family members. Participation can provide families with redress and allow them to represent the deceased, as well as being an important part of their grief process. It also helps to ensure a fair process, which has a positive impact on accountability and legitimacy. Family participation improves accountability by maximising the chance of achieving the right outcome via scrutiny, therefore identifying failures. Families also brings balance to the process, provide vital information about the deceased as well as helping to ensure that lessons are learned that will prevent future deaths. Death in Custody shows that procedural justice theory is relevant for participation in processes investigating human rights violations. It includes key recommendations on how to ensure participation can be fair and effective.
Part 1: The law -- Chapter 1. Requirement to Investigate Deaths in Custody -- Chapter 2. The Inquest System -- Part 2: Empirical research -- Chapter 3. Introducing the Empirical Research Approach -- Part 3: Participation benefits bereaved families -- Chapter 4. Legitimate Interests -- Chapter 5. Grief Process -- Chapter 6. Participation Provides Benefits to Families -- Part 4: Bereaved families holding the state to account -- Chapter 7. Instrumental Effect of Family Participation -- Chapter 8. Legitimacy Provided by Family Participation -- Chapter 9. Family Participation Benefits Accountability -- Part 5: Achieving fair and effective participation -- Chapter 10. Practical Challenges to Effective Participation -- Chapter 11. Practical Solutions -- Chapter 12. Conclusion.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Prisoners -- Death; Criminal law; Law, Criminal Law -- General; Prisons